دراسة العلاقة بين النفقات العمومية والنمو الاقتصادي دراسة حالة الجزائر من 1990- 2018 - رندة, بوحفص; حميدة, بوحنية; فوزية, سعد الله (University of eloued جامعة الوادي, 2020)
"تهدؼ ىذه الدراسة بشكل رئيسي, إلذ دراسة العلاقة بتُ النفقات العمومية والنمو الاقتصادي خلاؿ الفتًة 2018 (,لتحقيق ىذا ابؽدؼ تم تقسيم ىاتو الدراسة إلذ فصلتُ: الفصل الأوؿ تم فيو التطرؽ إلذ بعض ابؼفاىيم _1990( الأساسية حوؿ النفقات والنمو الاقتصادي, والفصل الثاني تم فيو اختبار العلاقة ما بتُ النمو والنفقات بالاعتماد على التقنيات ابغديثة في برليل السلاسل الزمنية مثل اختبار الإستقرارية لديكي فويلر, اختبار التكامل ابؼتزامن لابقل غربقر واختبار السببية بدفهو غربقر. وقد دلت نتائج الدراسة على أف ابؼتغتَين مستقرين في الفروؽ الأولذ ,واف النمو الاقتصادي متكامل زمنيا مع النفقات, حيث أف الزيادة في النمو تؤدي إلذ رفع حجم الإنفاؽ ,كما بينت النتائج أيضا غياب السببية بتُ ابؼتغتَين في ابؼدى القصتَ . ""The studay mainly aims to examine the relationship between public expenditures and the economic growth during the period(1990_2018).To achieve this goal, the study was divided into two chapters: the first chapter discussed some basic concepts about expenditures and the economic growth, the second chapter tested the relationship between growth and the expenditure based on modern techniques in the analysis of time series like the stationarity test of dickey fuller , engle granger cointegration test and the granger causality Test. The results of the study showd that the two variables are integrated of order one, and that economic growth is cointegrated with expenditures, and the increase in growth leads to an increase in the volume of spending, and the results also showed the absence of causality between the two variables in the short term. "
مذكرة ماستر اقتصادكمي
Keywords: النفقات العمومية، النمو الاقتصادي; public expenditures, Economic Growth, Simultaneous Integration, Error Correction Model, Causaling Angel and Granger.